Estudio de factibilidad de una granja piscícola ubicada en la finca La Rosa en el municipio de Hatonuevo, La Guajira, Colombia (2022)
Fish is one of the most consumed foods today due to its nutrients. Among them is the red tilapia, a spice widely consumed in Colombia, with great demand and, in the same way, supply. However, due to multiple factors, this demand is not met by current supply. In this project, a feasibility study is carried out to determine the profitability of building a fish farm in the municipality of Hatonuevo, La Guajira, due to the fact that it presents a great unsatisfied demand and has optimal conditions for the breeding of this species.